Using Imagery Rescripting as an Early Intervention for Depression in Young People - Pile, Victoria; Smith, Patrick; Lau, Jennifer Y. F. (Frontiers in Psychiatry, 2021)
Innovation is urgently needed for school-based early interventions for depression. Imagery rescripting for aversive memories has been shown to be a valuable therapeutic approach in adults. Yet it is rarely applied to young people or to depression. This is surprising given that intrusive images of aversive memories are implicated in the development and maintenance of depression. We review the literature and describe the co-development of an imagery rescripting protocol for young people (age 16 to 18) with high symptoms of depression. To contextualize and illustrate this approach, we identify three themes of negative images emerging from the 37 participants who completed imagery rescripting and provide a detailed case example for each theme. The identified themes are failure, interpersonal adversity, and family conflict or disruption. Given that there is some therapist concern about using imagery rescripting, we highlight any reported negative consequences of engaging in imagery rescripting. We propose that imagery rescripting is an acceptable and potentially effective tool for early intervention in depression, which is significantly underutilized in current practice.